Regulation of extracellular matrix composition by fibroblasts during perinatal cardiac maturation. (August 2022) - Kuwabara, Jill T.; Hara, Akitoshi; Heckl, Jack R.; Peña, Brisa; Bhutada, Sumit; DeMaris, Regan; Ivey, Malina J.; DeAngelo, Lydia P.; Liu, Xiaoting; Park, Juwon; Jahansooz, Julia R.; Mestroni, Luisa; et al.
Abstract: Background: Cardiac fibroblasts are the main non-myocyte population responsible for extracellular matrix (ECM) production. During perinatal development, fibroblast expansion coincides with the transition from hyperplastic to hypertrophic myocardial growth. Therefore, we investigated the consequences of fibroblast loss at the time of cardiomyocyte maturation by depleting fibroblasts in the perinatal mouse. Methods and results: We evaluated the microenvironment of the perinatal heart in the absence of fibroblasts and the potential functional impact of fibroblast loss in regulation of cardiomyocyte cell cycle arrest and binucleation. Cre-mediated expression of diphtheria toxin A in PDGFRα expressing cells immediately after birth eliminated 70–80% of the cardiac fibroblasts. At postnatal day 5, hearts lacking fibroblasts appeared similar to controls with normal morphology and comparable numbers of endothelial and smooth muscle cells, despite a pronounced reduction in fibrillar collagen. Immunoblotting and proteomic analysis of control and fibroblast-deficient hearts identified differential abundance of several ECM proteins. In addition, fibroblast loss decreased tissue stiffness and resulted in increased cardiomyocyte mitotic index, DNA synthesis, and cytokinesis. Moreover, decellularized matrix from fibroblast-deficient hearts promoted cardiomyocyte DNA replication. While cardiac architecture was not overtly affected by fibroblast reduction, few pups survived past postnatal day 11, suggesting an overall requirement for PDGFRα expressing fibroblasts. Conclusions: These studies demonstrate the key role of fibroblasts in matrix production and cardiomyocyte cross-talk during mouse perinatal heart maturation and revealed that fibroblast-derived ECM may modulate cardiomyocyte maturation in vivo . Neonatal depletion of fibroblasts demonstrated that although hearts can tolerate reduced ECM composition, fibroblast loss eventually leads to perinatal death as the approach simultaneously reduced fibroblast populations in other organs. Graphical abstract: Unlabelled Image Highlights: Extracellular matrix (ECM) composition changes as the heart matures. Perinatal cardiac fibroblasts are responsible for postnatal collagen deposition. Fibroblast loss reduced ECM complexity and tissue stiffness in the perinatal heart. Fibroblast-modulated ECM resulted in increased mononucleated cardiomyocytes (CM). Our findings highlight the importance of fibroblast-secreted ECM in CM maturation.